Analysis of Stakeholder Behavior on the Successful Development of Active Alert Villages In Grobogan District - Basiroh, Umi Malikhatul; Musthofa, Syamsulhuda Budi; Shaluhiyah, Zahroh (Indonesian Journal of Global Health Research, 2024)
Alert villages are a strategic effort to accelerate the Millennium Development Goals (MDGs) . An alert village is also a village whose residents have the resources who are ready and willing to prevent and overcome health problems, emergencies and disasters in the village independently. This research aims to analyze stakeholder behavior towards the successful development of active alert villages in Grobogan Regency. This type of research is an observational survey with a cross sectional approach. The population of this research is all village head stakeholders in Grobogan Regency, totaling 277 people with the research sample determined purposively . and proportional sampling of 164 people. Data was collected using a questionnaire containing 15 knowledge questions, and 12 questions each for attitudes, infrastructure, support from health workers, support from community leaders, organizational commitment and stakeholder behavior. Frequency distribution analysis is descriptive, while the chi square statistical test and multiple logistic regression use a computer program. The research results show that stakeholder behavior is significantly related to the success of developing active alert villages in Grobogan Regency (p value 0.003). It is necessary to increase the commitment of stakeholder organizations (village heads) through various capacity increases such as training and guidance in the context of developing active alert villages in Grobogan Regency.